2005
DOI: 10.1111/j.1471-0528.2005.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Urogynaecology: Effect of tension‐free vaginal tape in women with a urodynamic diagnosis of idiopathic detrusor overactivity and stress incontinence

Abstract: Objective To determine the effect of tension-free vaginal tape (TVT) in women with idiopathic detrusor overactivity (DO) and urodynamic stress incontinence (USI) and to propose appropriate pre-operative counselling based on this information.Design Retrospective cohort study.Setting Urogynaecology Unit, District General Hospital, Kent.Population Fifty-one women (from a total of 344 women undergoing TVT) with urodynamic evidence of both DO and USI who underwent TVT insertion between November 1999 and March 2003.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 14 publications
2
45
0
2
Order By: Relevance
“…Anticholinergics are the treatment of choice for this complication with very good results [19] . Recently, it was demonstrated that more than 60% of women diagnosed urodynamically with detrusor overactivity and SUI experience complete resolution of urge symptoms following the TVT operation [22] . Further symptom improvement can be achieved with additional anticholinergic medication [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Anticholinergics are the treatment of choice for this complication with very good results [19] . Recently, it was demonstrated that more than 60% of women diagnosed urodynamically with detrusor overactivity and SUI experience complete resolution of urge symptoms following the TVT operation [22] . Further symptom improvement can be achieved with additional anticholinergic medication [22] .…”
Section: Discussionmentioning
confidence: 99%
“…(3) The median erosion after transobturator sling was reported to be 2.4% (range 0%-5.9%). (19) Previous studies have also reported mesh erosion ranging from 0% to 7.3%, (17,18) and the median postoperative groin or thigh pain at six months following transobturator tape was reported to be 0.9% (range 0.6%-5.1%). (17) Persistence of groin pain beyond the immediate postoperative period is a concern in TVT-O.…”
Section: Discussionmentioning
confidence: 99%
“…(19) Previous studies have also reported mesh erosion ranging from 0% to 7.3%, (17,18) and the median postoperative groin or thigh pain at six months following transobturator tape was reported to be 0.9% (range 0.6%-5.1%). (17) Persistence of groin pain beyond the immediate postoperative period is a concern in TVT-O. (6) In a retrospective study on TVT-O at our own centre involving 419 patients, groin pain was found to have persisted for up to six months in 3.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining patients (11.4%) had uSUI with DO and normal urodynamics. Although uSUI with DO is a challenging condition when planning surgical management for a patient with SUI, many studies have shown that surgical procedures for SUI are safe and effective in the setting of preoperative DO [16,17,18,19]. …”
Section: Discussionmentioning
confidence: 99%